Problems of Education Quality In Private Islamic Universities Through Organizational Culture and Total Quality Management - Maulana, Olan (International Journal on Advanced Science, Education, and Religion, 2025)
This study found that a strong organizational culture at An-Nur University, Lampung, plays a crucial role in improving educational quality. Values such as discipline, commitment to quality, and collaboration among academics shape behavioral patterns that support the achievement of institutional goals. The implementation of integrated quality management also makes a significant contribution through a system involving systematic planning, control, and evaluation. Integrated quality management at An-Nur University, Lampung, involves all relevant parties, from leaders to educators and education staff. The process of regular performance measurement, combined with the use of information technology in evaluation, improves the quality of teaching and learning. As a result, significant improvements have been seen in both academic and non-academic aspects. This study demonstrates that a strong organizational culture and integrated quality management can improve educational quality. Islamic universities are expected to develop organizational cultural values that support educational quality, such as collaboration and shared commitment. Furthermore, regular performance evaluation is necessary for continuous improvement and effective policy-making to improve academic quality. This research can also serve as a reference in developing educational policies in Indonesia.Organizational Culture